2019
DOI: 10.1002/jnr.24433
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative in vivo imaging of neuronal glucose concentrations with a genetically encoded fluorescence lifetime sensor

Abstract: Glucose is an essential source of energy for the brain. Recently, the development of genetically encoded fluorescent biosensors has allowed real time visualization of glucose dynamics from individual neurons and astrocytes. A major difficulty for this approach, even for ratiometric sensors, is the lack of a practical method to convert such measurements into actual concentrations in ex vivo brain tissue or in vivo. Fluorescence lifetime imaging provides a strategy to overcome this. In a previous study, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 60 publications
0
53
0
Order By: Relevance
“…The probe showed intensiometric response with about 3-fold fluorescence increase after glucose binding and had Kd of 7.7 mM, which is physiologically relevant. iGlucoSnFR-TS [186], also called Sweetie-TS, was created by replacing cpGFP with a pH-stable FP cpT-Sapphire. This probe is considered as a fluorescence lifetime sensor that allows the conversion of measurements into actual concentrations in vivo.…”
Section: Classification Of Cpfp-based Gefis By Analyte Measured Anmentioning
confidence: 99%
“…The probe showed intensiometric response with about 3-fold fluorescence increase after glucose binding and had Kd of 7.7 mM, which is physiologically relevant. iGlucoSnFR-TS [186], also called Sweetie-TS, was created by replacing cpGFP with a pH-stable FP cpT-Sapphire. This probe is considered as a fluorescence lifetime sensor that allows the conversion of measurements into actual concentrations in vivo.…”
Section: Classification Of Cpfp-based Gefis By Analyte Measured Anmentioning
confidence: 99%
“…It has been suggested that astrocytic glycogen indeed plays an important role in supporting neuronal energy needs; and a key phenomenon in this proposed neuro-metabolic coupling between the two cell types is the capacity of astrocytes to increase their ATP production in response to neuronal activity 6,7,8 . This hypothesis, known as astrocyte-neuron lactate shuttle (ANLS), is still under debate, because other work has provided evidence that neurons may also increase their own rate of glycolysis in response to stimulation 9,10 , reflecting the necessity of further methods and approaches to study neuro-glia interaction.…”
Section: +mentioning
confidence: 99%
“…These utilize microbial periplasmic binding proteins (PBPs) as the molecular recognition moiety and circularly permuted GFP or its analogs as the reporter moieties. The strategy has created sensors for glutamate (iGluSnFR 24 , SF-iGluSnFR 25 ), GABA (iGABASnFR) 26 , glucose (iGlucoSnFR 27 , iGlucoSnFR-TS 28 ), maltose 29 , and phosphonate 30 . Because of their basis on microbial proteins, they are bio-orthogonal to endogenous signaling pathways in model organisms, permitting both long-term in vivo expression and use alongside most relevant pharmaceuticals.…”
mentioning
confidence: 99%